(untitled) (World Bulletin of Social Sciences, 2022)
This research investigated the correlation between process optimization models and operational efficiency within manufacturing firms located in Rivers State, Nigeria. The study encompassed a population of 246 managers and supervisors from 25 manufacturing firms in the state. From this population, a total of 152 respondents were randomly selected using a simple random sampling technique. Data collection involved administering questionnaires directly to the respondents. The predictor variable, process optimization model, was operationalized through real-time optimization and maintenance optimization, while operational efficiency, the criterion variable, was assessed using cost minimization and capacity utilization metrics. Bivariate analysis, utilizing the Spearman Rank Order Correlation Coefficient, was conducted to determine the relationship between the process optimization model and operational efficiency. The findings indicated a significant and positive correlation between the dimensions of the process optimization model and measures of operational efficiency. Consequently, the study concluded that real-time optimization and maintenance optimization contribute to enhancing the operational efficiency of manufacturing firms. The study recommends that management in manufacturing firms prioritize optimal utilization of production time to improve operational efficiency, particularly in terms of capacity utilization.